2017
DOI: 10.1002/jor.23646
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of fracture healing by hydroxyapatite/collagen paste and bone morphogenetic protein‐2 evaluated using a rat femur osteotomy model

Abstract: In fracture treatment, biological bone union generally depends on the bone's natural fracture healing capacity, even in surgically treated cases. Hydroxyapatite/collagen composite (HAp/Col) has high osteoconductivity and stimulates osteogenic progenitors. Furthermore, it has the potent capacity to adsorb bone morphogenetic proteins (BMPs). In this study, we prepared an injectable HAp/Col paste and evaluated its augmentation of bone union. Furthermore, the effect of HAp/Col paste combined with BMP-2 was also ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Compared to the paste of HAP and COL that can physically disperse and its effect may decrease much faster than desired,68 the use of titanium coated with calcined HAP-COL provides both mechanical stability and rigidity of the fixing method, maintaining long-term osteoconductive properties 69. Furthermore, substituted HAP in physiological conditions continuously releases its ions,70 with specific effects in the bone biochemistry and homeostasis 71.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the paste of HAP and COL that can physically disperse and its effect may decrease much faster than desired,68 the use of titanium coated with calcined HAP-COL provides both mechanical stability and rigidity of the fixing method, maintaining long-term osteoconductive properties 69. Furthermore, substituted HAP in physiological conditions continuously releases its ions,70 with specific effects in the bone biochemistry and homeostasis 71.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, the adsorbability of alendronate and bone morphogenetic protein 2 (BMP‐2) to HAp/Col was demonstrated . We have reported that the adsorbability of BMP‐2 onto HAp/Col enables long‐term release and enhances the bone formation in rat bone defect model …”
mentioning
confidence: 99%
“…12 In our previous studies, the adsorbability of alendronate and bone morphogenetic protein 2 (BMP-2) to HAp/Col was demonstrated. [13][14][15] We have reported that the adsorbability of BMP-2 onto HAp/Col enables long-term release and enhances the bone formation in rat bone defect model. 15 The objective of the present study is to investigate the feasibility of local antibiotic administration in the acute phase of a traumatic osteomyelitis model in rats using HAp/Col as a drug delivery system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various materials have been developed for bone defect repair (Itoh, Kikuchi, Takakuda, et al, ). We selected the HAP/Col composite because of its usefulness in various experimental models (Jung et al, ; Schneiders et al, ; Tsuchiya et al, ; Wei et al, ), and as a carrier for various recombinant proteins (Itoh et al, ; Itoh, Kikuchi, Koyama, et al, ; Itoh, Kikuchi, Takakuda, et al, ; Maehara et al, ; Sotome et al, ). Moreover, HAP/Col has been used in the clinical field due to its structural similarities to natural bone (Sotome et al, ).…”
Section: Discussionmentioning
confidence: 99%